The use of mobile phones to support women's entrepreneurship in the Arab countries. Issue 4 (21st November 2016) - Ameen, Nisreen A.; Willis, Rob
Abstract : Purpose: This paper aims to investigate how mobile phones can be used to support women's entrepreneurship in Arab countries. The objective is to explore new ways to close the gender gaps in terms of entrepreneurship in these countries. Design/methodology/approach: The methodology used in this research is an in-depth analysis of the existing literature and recent reports on women's entrepreneurship and on the adoption and use of mobile phones in Arab countries. Findings: The findings of this research indicate that female Arab entrepreneurs are interested in using mobile phones. However, they have not yet realised the full potential of mobile technology in empowering them beyond its basic use. Several challenges facing women entrepreneurship in the Arab countries were identified. Mobile phones can be used to overcome these challenges. Research limitations/implications: This research is based on the collection and analysis of secondary data rather than primary data to support the findings. Practical implications: There is a need for collaboration between telecommunication companies operating in the Arab region and government initiatives to build a solid environment in which female Arab entrepreneurs can operate. Originality/value: This research provides new insights and recommendations for reducing the gender gaps in terms of entrepreneurship by using new and improved techniques to address women's needs for economic independence. This will also increase the profit gained by the telecommunication companies operating in Arab countries and bring additional income to this region.